Paradigma Islam Pluralis-Multikultural (Studi Analisa Pemikiran Ulil Abshar Abdalla dengan JIL) - Zulfa, Laila Ngindana (Universitas Wahid Hasyim Semarang, 2023)
The topic of pluralism-multiculturalism is increasingly being discussed and socialized considering that Indonesia is a plural and multi-cultural nation, Often this situation makes society often divided. Inevitably often cause riots, hostility and war. One of the initiators of Pluralism in Indonesia is Ulil Abshar Abdalla, he is often mentioned as the successor of Cak Nur (Nurcholis Madjid). Ulil also established a network called the Jaringan Islam Liberal (JIL) to channel and spread his ideas about liberalism. This research is a library research with a character study approach combined with hermeneutic. Liberal Islam Network (JIL) was established in Jakarta on August 21, 2001 using intellectual networks located in Jakarta, Yogyakarta, Makassar, Bandung and several other cities. The vision promoted by JIL is to present a more responsive and progressive theology with the key to freedom and liberation.